The Information Conveyed by Debt and Equity Announcements in Australia - Oraluck Arsiraphongphisit (The International Journal of Banking and Finance, 2008)
This paper aims to report the findings associated with the effects of share prices around the disclosure dates of four different debt-and-equity fund-raising events over a 12-year period from 1991 to 2003 in Australia. By applying the well-known event study approach, along with the data-trimming procedures, a new idea is to remove all known confounding events and make corrections for thin-trading bias. The observed statistically significant price effects are consistent with theories: a positive price effect is observed for straight-debt and private placements whereas negative price effects occur when convertible debt and rights issues are announced. The results pertaining to the private placement effect is reported for the first time on this market. These findings are consistent with leverage, agency, and asymmetric information theories. It is believed that this study contributes new evidence on private placements and other events adding to existing literature surrounding the matter at hand.